Le gisement paléolithique moyen de la grotte des Cèdres (Var) - Defleur, Alban; Crégut-Bonnoure, Évelyne (Documents d'archéologie française, 1995)
Situated in South-Western Provence in the massif of Sainte-Baume, some thirty kilometres from Marseille, the Grotte des Cèdres (Var) was first excavated during the 1950s. In 1987 re-excavation took place and comprised the reexamination of conserved standing stratification. This re-examination permitted the identification of two human occupation levels, both of short periods, situated in a cool environment at the end of the Middle Pleistocene. With the identification of a new lithic industry. the discovery of the largest quantity of Tahr Rissien remains in Europe belonging to a new species, and the determination of new sub-species of Rodents and Rabbit, this site is now to be placed amongst those of major importance for the Mediterranean Europe, which is further increased by the presence of a human remain.